الجناس في سورة الواقعة (دراسة تحليلية بديعية) - Rini, Fitri Setyo; Mulyanto, Dedi; Ridho, Arsyad Muhammad Ali; Zaki, Muhammad (Universitas Muhammadiyah Gorontalo, 2024)
This study aims to analyze the use of paronomasia (jinās) in Surah Al-Waqi'ah, focusing on its rhetorical and aesthetic functions. The primary problem addressed is understanding the impact of jinās on the beauty and eloquence of the Quranic text. The research seeks to explore how paronomasia enhances the meanings and messages within Surah Al-Waqi'ah. A qualitative research method was employed, utilizing library research to collect and analyze data from various literary and rhetorical sources, including Quranic exegesis, books on rhetoric, and other relevant texts. The findings indicate that jinās in Surah Al-Waqi'ah significantly contributes to the text's aesthetic appeal and clarity of meaning. Paronomasia serves to emphasize key concepts and create a rhythmic flow that enhances the reader's emotional and intellectual engagement with the text. The study concludes that understanding the use of rhetorical devices like jinās can deepen appreciation for the artistic qualities of Quranic verses and enrich the comprehension of their messages. Further research is recommended to explore the full extent of rhetorical devices in other Surahs to fully grasp their impact on audiences.